K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 12 2017

a. 2x-1-x2= -(x2-2x+1)=-(x-1)2

b. 8x3+y6=(2x)3+(y2)3

=(2x+y2)(4x2-2xy2+y4)

c. x2-16+4xy+4y2=(x2+4xy+4y2)-16

=(x+2y)2-16=(x+2y+4)(x+2y-4)

20 tháng 5 2018

a) x2 + 6x + 9 = x2 + 2 . x . 3 + 32 = (x + 3)2

b) 10x – 25 – x2 = -(-10x + 25 +x2) = -(25 – 10x + x2)

                         = -(52 – 2 . 5 . x – x2) = -(5 – x)2

c) 8x3 - 1/8 = (2x)3 – (1/2)3 = (2x - 1/2)[(2x)2 + 2x . 12 + (1/2)2]

                    = (2x - 1/2)(4x2 + x + 1/4) 

d)1/25x2 – 64y2 = (1/5x)2(1/5x)2- (8y)2 = (1/5x + 8y)(1/5x - 8y)

NM
23 tháng 8 2021

a.\(4xy-8x^3y=4xy\left(1-2x^2\right)\)

b.\(5\left(x^2-y^2\right)+16\left(x-y\right)=\left(x-y\right)\left[5\left(x+y\right)+16\right]\)

c.\(x^3-4x^2y+4xy^3=x\left(x-2y\right)^2\)

d.\(x^2-3x+2=\left(x-1\right)\left(x-2\right)\)

e.\(x^2y-2x^2+4y-8=\left(y-2\right)\left(x^2+4\right)\)

g. \(x^3+y^3+z^3-3xyz=\left(x+y\right)^3-3xy\left(x+y\right)+z^3-3xyz=\left(x+y+z\right)\left(x^2+y^2+z^2-xy-yz-xz\right)\)

1 tháng 10 2016

a) 8x2 + 4xy - 2ax - ay = (8x2 + 4xy) - (2ax + ay) = 4x(2x + y) - a(2x + y) = (4x - a)(2x + y)

b) 2xy - x2 - y2 = 16 - (-2xy + x2 + y2) = 42 - (x - y)2 = (4 - x + y)(4 + x - y)

c) x2 - y2 - 2yz - z2 = x2 - (y2 + 2yz + z2) = z2 - (y + z)2 = (z - y - z)(z + y + z)

23 tháng 10 2016

a) \(\left(x^2-2x+1\right)-\left(y^2+2y+1\right)\)

\(=\left(x-1\right)^2-\left(y+1\right)^2\)

\(=\left(x-y-2\right)\left(x+y\right)\)

23 tháng 10 2016

b) xy+y2 = y ( x + y )

c) \(=\left(x^2+4xy+4y^2\right)-25\)

\(=\left(x+2y\right)^2-5^2\)

\(=\left(x+2y+5\right)\left(x+2y-5\right)\)

29 tháng 7 2016

a.\(3x^2-11x+6\)

\(3x^2-9x-2x+6\)

=\(3x\left(x-3\right)-2\left(x-3\right)\)

=\(\left(x-3\right)\left(3x-2\right)\)

b\(8x^2+10x-3\)

=.\(8x^2-2x+12x-3\)

=\(2x\left(4x-1\right)+3\left(4x-1\right)\)

=\(\left(4x-1\right)\left(2x+3\right)\)

d.\(x^2-y^2+10x-6y+16\)

=\(\left(x^2+10x+25\right)-\left(y^2+6y+9\right)\)

=\(\left(x+5\right)^2-\left(y+3\right)^2\)

=\(\left(x+5-y-3\right)\left(x+5+y+3\right)\)

=\(\left(x-y+2\right)\left(x+y+8\right)\)

e.\(x^4+x^2y^2+y^4\)

=\(x^4+2x^2y^2+y^4-x^2+y^2\)

=\(\left(x^2+y^2\right)^2-x^2y^2\)

=\(\left(x^2+y^2-xy\right)\left(x^2+y^2+xy\right)\)

29 tháng 7 2016

a)

\(=3x^2-9x-2x+6=3x\left(x-3\right)-2\left(x-3\right)=\left(x-3\right)\left(3x-2\right)\)

17 tháng 7 2017

a) \(x^6-y^6=\left(x^3\right)^2-\left(y^3\right)^2\)

                  \(=\left(x^3+y^3\right)\left(x^3-y^3\right)\)

                  \(=\left(x+y\right)\left(x-y\right)\left(x^2+xy+y^2\right)\left(x^2-xy+y^2\right)\)

b) sửa đề nhé!

\(6x-9-x^2=-\left(x^2-6x+9\right)\)

                       \(=-\left(x-3\right)^2\)

30 tháng 7 2018

b)  \(64x^3+1=\left(4x+1\right)\left(16x^2-4x+1\right)\)\

c) \(x^3y^6z^9-125=\left(xy^2z^3-5\right)\left(x^2y^4z^6+5xy^2z+25\right)\)

d)  \(27x^6-8x^3=x^3\left(27x^3-8\right)=x^3\left(3x-2\right)\left(9x^2+6x+4\right)\)

e)  \(x^6-y^6=\left(x^3-y^3\right)\left(x^3+y^3\right)=\left(x-y\right)\left(x^2+xy+y^2\right)\left(x+y\right)\left(x^2-xy+y^2\right)\)

64x3 + 1

= ( 4x )3  +  1

= ( 4x + 1 ) ( 16x2 - 4x + 1 )

Hằng đẳng thức 6 : A3 + B3

27x6 - 8x3

= ( 3x2)3 + ( 2x )3

= ( 3x + 2x ) ( 9x2 - 6x + 4x2 )

HĐT 6

x6 - y6

= ( x2 )3 - ( y2 )3

= ( x2 - y2 ) ( x4 + x2y2 + y4 )

HĐT 7 : A3 - B3

x3y6z9 + 1

= ( xy2z3)3 + 1

= ( xy2z3 + 1 ) ( x2y4z6 + zy2z3 + 1 )

HĐT 6